Governing Infrastructure Regulators in Fragile Environments : Principles and Implementation Manual - World Bank (Washington, DC: World Bank, 2019)
Countries exiting conflict and fragility face many urgent priorities and almost invariably suffer from substantial infrastructure deficits. There is typically very little infrastructure investment during periods of fragility and conflict, and existing installations are often damaged or destroyed. The purpose of this manual is to contribute to improvements in the quality of infrastructure regulation. It does so by identifying key principles for the governance of infrastructure regulators and by suggesting how these principles can be introduced successfully and maintained over time. The introduction of cross-cutting governance principles for regulators is based on the assumption that a uniform set of governance principles can be less costly and complex for governments to implement and enforce and will provide potential investors with a more consistent and predictable regulatory environment to navigate. The manual also discusses the process of implementing regulatory governance reforms in fragile contexts. Improvements in governance frameworks for infrastructure regulators will support better and accountable regulatory decision-making, as well as increased investment and overall economic development. Case studies from relevant country experience complement and provide context to the discussion on principles.